Pengaruh Penerapan Model Pembelajaran KooperatifTipe Student Teams Achievement Division terhadapPemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 23 Padang - NONSRI MARDAYANI (Jurnal Edukasi dan Penelitian Matematika, 2020)
Understanding mathematical concepts is one of  the goals of mathematics learning that student must have. However, the facts on the ground show that the understanding of the mathematical concepts of grade VIII students of SMPN 23 Padang is still low. Efforts are made to improve students’ understanding of concepts bt applying the cooperative learning model type Student Teams Achievement Division (STAD) in mathematics learning. The purpose oh this is to describe the understanding oh mathematical concepts of students who learn using STAD type cooperative learning models better than students who learn to use conventional learning models in class  VIII SMPN 23 Padang. This type of  research is quasy experiment with a static group design. Based on the results of data analysis, it is found that understanding mathematical concepts of students who learn using the STAD type cooperative learning model is better than students who learn with conventional learning. So it can be concluded that the cooperative type STAD model has an influence on the understanding of mathematical concepts of students. Keywords— Concept Cooperative Learning, Student Teams Achievement Division, Understanding of Mathematical